2019
DOI: 10.1007/s00268-019-05057-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes with Semi‐mechanical and Circular Stapled Intrathoracic Esophagogastric Anastomosis following Esophagectomy

Abstract: Background Several techniques have been described for esophagogastric anastomosis following esophagectomy. This study compared the outcomes of circular stapled anastomoses with semi-mechanical technique using a linear stapler. Methods Perioperative data were extracted from a contemporaneously collected database of all consecutive esophagectomies for cancer with intrathoracic anastomoses performed in the Trent Oesophago-Gastric Unit between January 2015 and April 2018. Anastomotic techniques: circular stapled v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Furthermore, metanalyses for open esophagectomy have stated that the patients receiving LS anastomoses after esophagectomy tend to have fewer anastomotic strictures in comparison to the patients receiving CS anastomoses while having similar rates of anastomotic insufficiencies [ 22 , 23 ]. Yanni et al even displayed higher rates in anastomotic insufficiency in the patients receiving CS when compared to LS [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, metanalyses for open esophagectomy have stated that the patients receiving LS anastomoses after esophagectomy tend to have fewer anastomotic strictures in comparison to the patients receiving CS anastomoses while having similar rates of anastomotic insufficiencies [ 22 , 23 ]. Yanni et al even displayed higher rates in anastomotic insufficiency in the patients receiving CS when compared to LS [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study compared intrathoracic SSLS (n = 74) with CS (n = 85) anastomosis, and found that employing a semimechanical side-to-side esophagogastric anastomosis significantly reduced the rate of leaks (4.1% vs. 15.3%, P = 0.019). 115 In our study comprising a larger number of patients undergoing esophagectomy with intrathoracic anastomosis we found that HS (OR = 1.73) and SSLS (OR = 1.68) anastomoses were associated with a significantly higher risk of anastomotic leak than CS anastomosis.…”
Section: Discussionmentioning
confidence: 53%
“…Blackmon et al15 performed a propensity-matched analysis of 3 techniques for intrathoracic esophagogastric anastomosis (23 patients in each group) and showed similar leak rates after SSLS (8.7%), CS (4.3%), and HS (4.3%) anastomosis ( P =0.78). Another study compared intrathoracic SSLS (n=74) with CS (n=85) anastomosis, and found that employing a semimechanical side-to-side esophagogastric anastomosis significantly reduced the rate of leaks (4.1% vs. 15.3%, P =0.019) 115. In our study comprising a larger number of patients undergoing esophagectomy with intrathoracic anastomosis we found that HS (OR=1.73) and SSLS (OR=1.68) anastomoses were associated with a significantly higher risk of anastomotic leak than CS anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…The linear stapling technique is a side-to-side anastomosis between the esophagus and the conduit, which has been reported to be functionally favorable with a larger diameter of the anastomosis that offers easy passage of the intraluminal content and reduced circular pressure at the anastomosis site. These factors might explain the low incidence of anastomotic leakage and strictures [ 21 - 23 ].…”
Section: Discussionmentioning
confidence: 99%